2004
DOI: 10.1007/s10157-004-0306-y
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged membranous lupus nephritis with change of anti-ssDNA antibody titer and repeated renal relapse

Abstract: We report a case of a 44-year-old woman with nephrotic syndrome who underwent renal biopsy three times. On each occasion, light microscopy showed membranous nephropathy with mild to moderate thickening of the glomerular capillary walls. Immunofluorescence microscopy showed predominant deposition of immunoglobulin (Ig) G, IgG1, IgG2, IgG3, and IgG4; C3; and C1q along the glomerular capillary walls and deposition of IgM and IgA in some parts of the walls. Electron microscopy revealed the accumulation of electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…An interesting point is that this patient only had high anti-dsDNA titre and low C3 level 2 years after initial presentation. Yumura et al reported a 44-year-old woman with similar presentation in Japan [15]. Our patient first exhibited nephrotic syndrome at the age of 14, when she had borderline titre of anti-dsDNA and had no hypocomplementemia.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…An interesting point is that this patient only had high anti-dsDNA titre and low C3 level 2 years after initial presentation. Yumura et al reported a 44-year-old woman with similar presentation in Japan [15]. Our patient first exhibited nephrotic syndrome at the age of 14, when she had borderline titre of anti-dsDNA and had no hypocomplementemia.…”
Section: Discussionmentioning
confidence: 61%
“…Although most patients with lupus nephritis exhibit active lesions histologically with high anti-dsDNA titre, patients with membranous lupus nephritis may have less active histological findings and are often negative for anti-dsDNA [15,16]. The titre of anti-single-stranded DNA (anti-ssDNA) antibody was suggested by some authors to better co-relate with renal disease activity than anti-dsDNA [15,17]. However, studies in this field are limited, and hopefully, more information will be available in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some patients with "full-house" nephropathy were found to develop SLE several years later (5,6). In some SLE patients the histopathologic features of lupus nephritis on renal biopsy were not observed, while accompanying IgA nephropathy was diagnosed (7).…”
Section: Systemic Lupus Erythematosus (Sle) Is An Autoimmune Disease mentioning
confidence: 99%
“…However, we have chosen to investigate anti-ssDNA antibodies, which present in 30–70% of patients, based on data indicating that they are hydrolytic, nephritogenic, and may serve as strong predictors of flare [3, 4, 2628]. The significance of anti-ssDNA antibodies in SLE is further supported by data indicating that they are still present after treatment with immunosuppressive therapy which eliminates anti-dsDNA antibodies, investigations in mouse models of nephritogenic lupus in which only anti-ssDNA antibodies were found, and findings that some anti-dsDNA antibodies are not pathogenic [6, 7, 19, 27, 29, 30]. …”
Section: Introductionmentioning
confidence: 99%